العوامل المؤثرة على رغبة المشروعات الصغيرة والمتوسطة في تطبيق نظم المعلومات المحاسبية (دراسة ميدانية على المشروعات الصغيرة والمتوسطة في سورية) - كاشاني بور, محمد; خنیفر, حسین; باقر جعفري, سید محمد; رحيميان, نظام الدين; حمود, مريم (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدف هذا البحث إلى دراسة العوامل المؤثرة على رغبة المشروعات الصغيرة والمتوسطة في تطبيق نظم المعلومات المحاسبية حيث اعتمدت الباحثة على أسلوب تحليل المضمون من خلال مراجعة المقالات والأدبيات السابقة المتعلقة بالبحث وإجراء مقابلات مع عينة من مديري المشروعات المتوسطة كما اعتمدت على أسلوب الاستقصاء (استبانة) كأداة بحثية لجمع البيانات ومن خلال تحليل البيانات التي تم جمعها تم التوصل لمجموعة من النتائج منها : - وجود رغبة لدى 61.7% من المشروعات في تطبيق نظم معلومات محاسبية متطورة تلبي احتياجات السوق والمشروع في آن واحد في حين 38.3% لا ترى حاجة لتطبيق هذه النظم . - وجدت الباحثة أن عوامل ( العمر – النوع – الربحية – السيولة – الحجم – تكنولوجيا المعلومات – مشاركة المدير في تنفيذ نظم المعلومات – المعرفة بنظم المعلومات – المعرفة بالمحاسبة – توافق النظام المستخدم – المنافسة ) ذات تأثير معنوي ذو دلالة إحصائية على رغبة المشروعات الصغيرة والمتوسطة في تطبيق نظم المعلومات المحاسبية في حين أن عاملي ( الخبرة الخارجية والداخلية – الدعم الحكومي) لا تؤثر معنوياً على الرغبة. أوصت الدراسة بالعمل على إيجاد آلية لتوضيح أهمية تطبيق نظم المعلومات المحاسبية في منشآت الأعمال وضرورة توفير الخبرات والترويج لها وزيادة الدعم الحكومي لقطاع المشروعات الصغيرة والمتوسطة من خلال استصدار القوانين والتشريعات التي تسهل عمل هذه المشروعات وإجراء دراسة موازية لمدى جودة تطبيق هذه النظم. This study aims to study the factors influencing the willingness of small and medium enterprises in the application of accounting information systems. The researcher relied on the method of content analysis by reviewing the previous articles and literature related to research and conducting interviews with a sample of the medium managers. The questionnaire was also used as a research tool To collect the data and through the analysis of the data collected, a number of results were reached, including: - 61.7% of projects want to apply accounting information systems to meet the needs of the market and the project at the same time, while 38.3% do not see the need to apply these systems.. - The researcher found that the factors (age - type - profitability - liquidity - size - IT - the participation of the manager in the implementation of information systems - knowledge of information systems - knowledge of accounting - the compatibility of the system used - competition) has a significant impact on the willingness of small and medium enterprises In the application of accounting information systems while the factors (external and internal experience - government support) do not significantly affect the willingness . The study recommended the establishment of a mechanism to clarify the importance of applying accounting information systems in business establishments and the necessity of providing expertise and promoting them and increasing governmental support for the SME sector through issuing laws and legislations that facilitate the work of these projects.